Teaching readers of English students, texts, and contexts - Hedgcock, John; Ferris, Dana (New York Routledge, 2018)
"A comprehensive manual for pre- and in-service ESL, EFL, and EIL educators who work with multilingual students at the secondary and post-secondary levels, this text balances insights from reading theory and research with highly practical, field-tested strategies for teaching and assessing second-language reading that educators can readily adopt and adapt to suit their contexts and student populations. Teaching Readers of English is a complete "go-to" source for teaching reading and promoting classroom and professional literacies in an increasingly digital world. Offering principled approaches and methods for planning and delivering effective L2 reading instruction, the text includes pedagogical features such as questions for reflection, further reading and resources, and application activities to develop purposeful classroom reading lessons in a range of contexts"--Provided by publisher.
Foundations of l1 and l2 literacy, reading, and learning to read -- L2 reading: focus on the reader -- L2 reading: focus on the text -- Vocabulary learning and teaching in l2 reading instruction -- Reading closely: designing an intensive reading lesson -- Reading for quantity: extensive reading -- Syllabus design and instructional planning for the l2 reading course -- Classroom l2 reading assessment.
Includes bibliographical references (pages 361-405) and indexes.
Keywords: English language -- Study and teaching -- Foreign speakers; Reading; Second language acquisition; Curriculum planning; Reading teachers